STUDY OF CERTAIN ASPECTS OF THE CONSTITUTIONAL AND LEGAL MECHANISM OF ELECTION FINANCING - Вигівська, А. С. (Київський національний університет імені Тараса Шевченка, 2021)
The article is devoted to the study of constitutional and legal mechanisms of financing the elections to the Parliament of Ukraine with the application of the recommendations of the Council of Europe. This applies to the funds used to hold elections, as well as to change the principle of financing elections with the involvement of various sources. The Electoral Code of Ukraine is analyzed as a normative act that contains current trends in European suffrage.

Стаття присвячується дослідженню конституційно-правових механізмів фінансування виборів до парламенту України із застосуванням рекомендацій Ради Європи. Це стосується коштів за рахунок яких здійснюються вибори, а також зміну принципу фінансування виборів із залученням різних джерел. Аналізується Виборчий Кодекс України як нормативний акт, що вміщує сучасні тенденції європейського виборчого права.
ДОСЛІДЖЕННЯ ОКРЕМИХ АСПЕКТІВ КОНСТИТУЦІЙНО-ПРАВОВОГО МЕХАНІЗМУ ФІНАНСУВАННЯ ВИБОРІВ
Keywords: elections; political parties; election financing mechanism; sources of financing; Council of Europe.; вибори; політичні партії; механізм фінансування виборів; джерела фінансування; Рада Європи.